Noonan-Like Syndrome with Loose Anagen Hair: Genetic and Phenotypic Variability, Differential Diagnosis - Svetlana Ya. Volgina; Yosuman S. Kurbanova; Aydamir Sh. Abubakarov; Arip M. Nimatulaev; Ekaterina A. Nikolaeva; Rimma G. Gamirova (Вопросы современной педиатрии)
The review summarizes the data on Noonan-like syndrome with loose anagen hair (NSLH) from the group of RASopathies. The genetic aspects of the syndrome, its pathogenesis, clinical signs, and comorbitant conditions are considered. Particular attention is paid to the differential diagnosis between two genetically heterogeneous types of NSLH associated with mutations in the SHOC2 gene (NSLH1) and in the PPP1CB gene (NSLH2). Clinical case description of the patient with confirmed NSLH1 is presented. This review is intended to increase physicians’ awareness specifically on NSLH genotype-phenotype correlations. This is crucial for genetic counseling, diagnosis, and development of new management and rehabilitation methods.